An Integrative Approach to Innovation Management Patterns of Companies$1 (BInnovation Orientation and Customer Responses to Product Program Innovativeness /s - Zacharias, Nicolas; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
Despite the critical role that managers ascribe to innovation, the high failure rates of newly introduced products indicate that success is difficult to achieve. Nicolas Zacharias addresses this challenge using an integrative approach that deals with the complex organizational antecedents and the customer-related outcomes of product program innovativeness. In his empirical analyses with data from B2B companies, he identifies four different types of innovation orientation and shows that the most innovative companies are financially not the most successful. Furthermore, he investigates positive and negative customer responses to different dimensions of innovativeness as well as contingencies that might alter these linkages.
Keywords: Economics; Economics/Management Science; Innovation/Technology Management